2017
DOI: 10.1037/abn0000220
|View full text |Cite
|
Sign up to set email alerts
|

A psychometric investigation of gender differences and common processes across borderline and antisocial personality disorders.

Abstract: The comorbidity between Borderline Personality Disorder (BPD) and Antisocial Personality Disorder (ASPD) is well-established, and the two disorders share many similarities. However, there are also differences across disorders: most notably, BPD is diagnosed more frequently in females and ASPD in males. We investigated if a) comorbidity between BPD and ASPD is attributable to two discrete disorders or the expression of common underlying processes, and b) if the model of comorbidity is true across sex. Using a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 83 publications
(135 reference statements)
0
7
0
Order By: Relevance
“…A previous study on the joint structure of ASPD and BPD criteria suggested that an overarching general dimension of risk for all the criteria plus other psychopathology exists (Chun et al, 2017). Similarly, our investigation underscored the importance of such an overarching dimension of risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study on the joint structure of ASPD and BPD criteria suggested that an overarching general dimension of risk for all the criteria plus other psychopathology exists (Chun et al, 2017). Similarly, our investigation underscored the importance of such an overarching dimension of risk.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the etiologic factors of ASPD and BPD appear to form a hierarchy of highest, intermediate, and lowest level of generality, as expressed in bifactor models (Figure 1a). Diagnoses of ASPD and BPD share genetic etiology with each other and with other related PDs, but they also have independent genetic influences (Chun et al, 2017; Reichborn-Kjennerud et al, 2015; Torgersen et al, 2008). Specific criteria for ASPD (respectively BPD) share many genetic influences, but also they have specific (i.e., criterion- specific) genetic and environmental influences (Kendler et al, 2012; Reichborn-Kjennerud et al, 2013; Rosenström et al, 2017).…”
mentioning
confidence: 99%
“…It is estimated that 0.2−3.3% of the population are affected by ASPD 1 ; however, estimates vary markedly by gender as well as population. For example, ASPD is diagnosed more frequently in men than in women 2 . Population estimate for men was 5.5%; for women, it was 1.9% 3 .…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only one study included an investigation of the VDT's factor structure (Edwards et al, 2017); however, only a joint DT-VDT model was tested using confirmatory factor analysis (CFA), and the joint model obtained a questionable fit (e.g., comparative fit index <0.90 and root mean square error of approximation >0.10; Hu & Bentler, 1999). Chun, Harris, Carrion et al (2017) tested the joint structure of borderline personality disorder and antisocial personality disorder in a sample of drug users, and found that a bifactor model with two group factors provided the best fit; however, their study did not focus on the VDT as it did not include the third component, vulnerable narcissism.…”
Section: Introductionmentioning
confidence: 99%
“…Chun, Harris, Carrion et al . (2017) tested the joint structure of borderline personality disorder and antisocial personality disorder in a sample of drug users, and found that a bifactor model with two group factors provided the best fit; however, their study did not focus on the VDT as it did not include the third component, vulnerable narcissism.…”
Section: Introductionmentioning
confidence: 99%